Depriving Right-Holders of Fundamental Rights and Freedoms Too Easily? Low Volume Vehicle Technical Association Inc v Brett and the Issue of Waiver under the New Zealand Bill of Rights Act 1990 - Laugesen, Rosa (Victoria University of Wellington Law Review, 2020)
In Low Volume Vehicle Technical Association Inc v Brett, the New Zealand Court of Appeal grappled with the rare issue of whether a person can waive their right to freedom of expression under the New Zealand Bill of Rights Act 1990 (NZBORA). The Court, responding in the affirmative, concluded that Mr Brett had waived this right. This article critiques that decision. While the Court was right to find that Mr Brett could waive his right to freedom of expression, it failed to scrutinise the waiver to ensure that this relinquishment of a protected right in fact reflected Mr Brett's free choice. Had the Court considered a different approach to analysing Mr Brett's waiver – at the prima facie breach stage, instead of under s 5 of the NZBORA – proper scrutiny would have been achieved. That approach would have ensured that Mr Brett was not so easily deprived of his right.